2022
DOI: 10.1021/acsami.2c02295
|View full text |Cite
|
Sign up to set email alerts
|

Rutin-Loaded Stimuli-Responsive Hydrogel for Anti-Inflammation

Abstract: An active flavonoid compound rutin was incorporated into a guanosine phenylborate hydrogel (GBR) by a stimuli-responsive borate ester linkage for the treatment of inflammatory bowel disease (IBD). The components and morphology of the drug delivery system were characterized by NMR, UV–vis spectroscopy, and AFM. Rheological measurements revealed the required injectability and self-healing ability, which contributed to its application in rectal administration. The cell assays proved the excellent compatibility an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 51 publications
(72 reference statements)
0
21
0
Order By: Relevance
“…Dynamic borate ester bonds can break under varying external environments, such as pH, H 2 O 2, and glucose, and thus have different corresponding responsive properties. 41,42 Given the antitumor pharmacological effects of Dfu, Cap, Aza, and Flu and the acidic microenvironment of tumors, together with the responsiveness of borate ester bonds, the drug release behavior of the GBDfu hydrogel was explored under different pH conditions. The Dfu content in the drug-release system was determined by HPLC according to the standard curve of the drug (Fig.…”
Section: Drug Release Properties Of the G-based Hydrogelsmentioning
confidence: 99%
“…Dynamic borate ester bonds can break under varying external environments, such as pH, H 2 O 2, and glucose, and thus have different corresponding responsive properties. 41,42 Given the antitumor pharmacological effects of Dfu, Cap, Aza, and Flu and the acidic microenvironment of tumors, together with the responsiveness of borate ester bonds, the drug release behavior of the GBDfu hydrogel was explored under different pH conditions. The Dfu content in the drug-release system was determined by HPLC according to the standard curve of the drug (Fig.…”
Section: Drug Release Properties Of the G-based Hydrogelsmentioning
confidence: 99%
“…To design hydrogels with smart on-demand drug release capabilities, drugs are either covalently attached to the hydrogel backbone via a stimuli sensitive linker or physically entrapped in a hydrogel that has a stimuli sensitive backbone. For example, a plant-based antioxidant compound (rutin) was attached to the hydrogel carrier via borate ester linkage for pH and reactive oxygen species (ROS) responsive drug release for the treatment of IBD . In another study, an HIV fusion inhibitor (Enfuvirtide) was attached to the hydrogel backbone via a prostate specific antigen (PSA) labile linker for seminal fluid responsive delivery to prevent heterosexual HIV transmission in women. , Carboxymethyl chitosan-based hydrogels show pH responsive swelling, and a study has shown higher bovine serum albumin (BSA) release in basic pH as opposed to acidic pH where the BSA was physically entrapped in the hydrogel .…”
Section: Formulation Strategiesmentioning
confidence: 99%
“…A G-quadruplex hydrogel consists of four guanosine moieties held via an intermolecular Hoogsteen-type H-bond which further self-assembles to form a higher-order structure by π–π stacking interaction . Since Davis et al developed the K + -templated guanosine–borate G-quartet hydrogel, , such guanosine–borate-based G-quadruplex hydrogels have been extensively studied by the researchers and utilized for various applications. , Chen et al have designed an isoguanosine–borate–guanosine-based hydrogel and demonstrated its dual functional properties as a drug carrier as well in vivo anti-tumor activity . Recently, a G-quadruplex hydrogel derived from the self-assembly of guanosine, 2-formylphenylboronic acid, and putrescine was used as a cascade reaction container to produce reactive oxygen species (ROS) from glucose.…”
Section: Introductionmentioning
confidence: 99%